2000
DOI: 10.1051/m2an:2000156
|View full text |Cite
|
Sign up to set email alerts
|

existence of solutions for an elliptic-algebraic system describing heat explosion in a two-phase medium

Abstract: Abstract. The paper is devoted to analysis of an elliptic-algebraic system of equations describing heat explosion in a two phase medium filling a star-shaped domain. Three types of solutions are found: classical, critical and multivalued. Regularity of solutions is studied as well as their behavior depending on the size of the domain and on the coefficient of heat exchange between the two phases. Critical conditions of existence of solutions are found for arbitrary positive source function.Mathematics Subject … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2001
2001
2001
2001

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The main difference is that stationary solutions of (1.1)-(1.3) can lose their regularity. We show [7] that there are three types of solutions of (1.1)-(1.3): classical solutions, for which u 1 (x) < u * 1 inΩ; critical solutions, for which u 1 (x) 6 u * 1 inΩ, and the critical set Ω * = {x ∈ Ω : u 1 (x) = u * 1 } is not empty; and multi-valued solutions for which u 1 (x) can take values larger than u * 1 . It can easily be shown that the classical solutions are continuous, together with their second derivatives.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…The main difference is that stationary solutions of (1.1)-(1.3) can lose their regularity. We show [7] that there are three types of solutions of (1.1)-(1.3): classical solutions, for which u 1 (x) < u * 1 inΩ; critical solutions, for which u 1 (x) 6 u * 1 inΩ, and the critical set Ω * = {x ∈ Ω : u 1 (x) = u * 1 } is not empty; and multi-valued solutions for which u 1 (x) can take values larger than u * 1 . It can easily be shown that the classical solutions are continuous, together with their second derivatives.…”
Section: Introductionmentioning
confidence: 83%
“…The existence of stationary solutions for this case and blow-up solutions have been studied in detail [8][9][10][11][12][13][14][15]. We show that stationary solutions of (1.1)-(1.3) converge to stationary solutions of (1.5) as α → ∞ [7].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations